2018
DOI: 10.1016/j.celrep.2018.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Transcriptional Repression by BCL6 Confers Insulin Sensitivity in the Setting of Obesity

Abstract: SUMMARY Accumulation of visceral adiposity is directly linked to the morbidity of obesity, while subcutaneous body fat is considered more benign. We have identified an unexpected role for B cell lymphoma 6 (BCL6), a critical regulator of immunity, in the developmental expansion of subcutaneous adipose tissue. In adipocyte-specific knockout mice (Bcl6AKO), we found that Bcl6 deletion results in strikingly increased inguinal, but not perigonadal, adipocyte size and tissue mass in addition to marked insulin sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 74 publications
(85 reference statements)
2
28
0
Order By: Relevance
“…The phosphorylation of IRS1 at Ser307 site has been shown to impair insulin signaling (12,13), which was reported as one of the major postreceptor factors involved in IR in skin fibroblasts and skeletal muscle cells from patients with PCOS (3,9,32). The phosphorylation of IR-b Tyr1150/115, the phosphorylation of IRS1/2 Tyr612, and the phosphorylation of Akt Ser473 were important insulin signaling molecules (33)(34)(35)(36)(37). Here, we found that the insulin-induced Ser307 19).…”
Section: Discussionmentioning
confidence: 58%
“…The phosphorylation of IRS1 at Ser307 site has been shown to impair insulin signaling (12,13), which was reported as one of the major postreceptor factors involved in IR in skin fibroblasts and skeletal muscle cells from patients with PCOS (3,9,32). The phosphorylation of IR-b Tyr1150/115, the phosphorylation of IRS1/2 Tyr612, and the phosphorylation of Akt Ser473 were important insulin signaling molecules (33)(34)(35)(36)(37). Here, we found that the insulin-induced Ser307 19).…”
Section: Discussionmentioning
confidence: 58%
“…While this is likely the result of AGS adaptations in numerous proteins, the importance of the ATP5G1 variant is highlighted by our experimental evidence demonstrating improvement in spare respiratory capacity in mouse NPCs over-expressing AGS ATP5G1 variants and decreased spare respiratory capacity in AGS NPCs with ATP5G1 L32P knock-in. A critical role for ATP5G1 in cellular energetics is also supported by recent work uncovering ATP5G1 as one of the major effectors of the transcription factor, BCL6, in regulating adipose tissue energetics as well as maintaining thermogenesis in response to hypothermia (43, 44).…”
Section: Discussionmentioning
confidence: 84%
“…By RNA sequencing and promoter analysis, BCL6 was found to enhance the promoter activity of signal transducer and activator of transcription 1, and was identified as an upregulator of Zfp423, early B cell factor 1 (Ebf1), and PPAR . [32] However, in vivo model of conditional knockout of BCL6 in adipose tissues showed that BCL6 deletion would lead to WAT expansion, [33] implying that BCL6 possibly plays different roles in regulating early adipogenesis and late lipogenesis. From some RNA-seq data used to identify BCL6, we have also identified a novel transcription factor Zfp217 that regulates early adipogenesis of C3H10T1/2 cell line [25,34] (Figure 2), implying that the transcriptional atlas of commitment can be further improved.…”
Section: Transcription Factors Regulating Commitmentmentioning
confidence: 99%